Iscenesat affekt - Christiansen, Signhild Linderoth (Kvinder, Køn & Forskning, 2015)
The performance Cry Me a River (2010) by Anna Mendelssohn is a solo about inner and outer climate catastrophes. The act of crying is central, and emotions are treated explicitly during the performance. When affect is presented this way, it affects the whole dramaturgy as well as the relationship between the audience and the work of art. In the article key terms of the affect theory by Sara Ahmed are applied in an analysis and a discussion of the performance. Affect appears as a cultural and relational phenomenon, and “thought”, “sensation” and “emotion” always exist simultaneously. The article suggests that critical affect theory offers theoretical tools for communicating about emotions in art. It also suggests and that affect theory is useful in the development of feminist theories concerning the encounter between audience/scientist and art, as it describes how emotions always emerge midway between subject and object, and always are related to structures of power.